Nghiên cứu lý thuyết cơ chế phản ứng oxi-đêhiđro hóa propan trên xúc tác V2O5(001) bằng phương pháp phiến hàm mật độ sử dụng sóng phẳng và thế giả. - Hà, Nguyễn Ngọc; Thọ, Nguyễn Minh; Huế, Trần Thành (Vietnam Journal of Chemistry, 2012)
The reaction kinetics of the oxidative dehydrogenation of propane was studied by using periodic density functional theory with a plane-waves basis set and pseudopotential. The reaction proceeds via a Mars - van Krevelen redox mechanism and its elementary steps are identified, the activation of propane has been found to be the rate determining step.